ARSENIC-BEARING CARBONATE WATERS: GEOCHEMICAL AND THERMODYNAMIC ANALYSIS OF THEIR GENESIS, TRANSFORMATION OF ARSENIC MIGRATION SPECIES, AND MODELS FOR THE GENESIS OF HYDROGENIC AS SULFIDE MINERALIZATION - Krainov S.R.; Ryzhenko B.N.; Cherkasova E.V. (My University, 2007)
Analysis of hydrogeochemical materials on As distribution in CO2-bearing (carbonate) waters in various regions and the thermodynamic simulation of geochemical processes in rock-CO2-bearing water systems made it possible to constrain the optimal conditions for As transfer from rocks into carbonate waters and the accumulation of this element in the waters. The problem was solved with regard for the various rates of As transitions from rocks to water: (a) high rates of As transitions from rocks in compliance with the ion exchange mechanism and (b) low rates of As transitions from rocks in compliance with the mechanism involving the decomposition of As-bearing minerals. Various mechanisms of As extraction from rocks result in the compositional diversity of the aqueous phase and various As migration species in CO2-bearing waters, which, in turn, control the equilibrium concentration levels of this element. The principally important boundary conditions of As enrichment in CO2-bearing waters are high and R/W ratios in the geochemical systems, a preliminary increase in the Cl concentration in the CO2-bearing waters, and the origin of these waters at high-density heat fluxes. As migration species were simulated for the model solutions and real carbonate waters of various geochemical types, and it is demonstrated that the predominant As species are oxygen-bearing HAsO 02 , and AsO −2 at a subordinate role of the sulfide HAs2S 2−4 , and As2S 2−4 — species even at high Σ S2− in the system. Two models of the genesis of solid As sulfides in CO2-bearing waters are analyzed: (1) with oxygen-bearing species (HAsO 02 , and AsO −2 ), which occur most widely, and (2) with sulfide species (As2S 2−4 , HAs2S −4 , and As4S 2−7 ), which occur not as widely.